2008
DOI: 10.1002/bdra.20491
|View full text |Cite
|
Sign up to set email alerts
|

Folate‐related gene polymorphisms as risk factors for cleft lip and cleft palate

Abstract: BACKGROUND-Cleft lip with or without cleft palate (CLP) and cleft palate only (CPO) have an inherited component and, many studies suggest, a relationship with folate. Attempts to find folaterelated genes associated with clefts have, however, often been inconclusive. This study examined four SNPs related to folate metabolism (MTHFR 677 C→T, MTHFR 1298 A→C, MTHFD1 1958 G→A, and TC II 776 C→G) in a large Irish population to clarify their relationship with clefts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
2
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 38 publications
4
57
2
9
Order By: Relevance
“…Folate has long been considered one such factor in number of observational studies. [2][3][4][5]7,8,15,31 Maternal folic acid supplementation in early pregnancy has been suggested to play a role in the prevention of nonsyndromic orofacial cleft, i.e. cleft lip with or without cleft palate (CL/P).…”
Section: Discussionmentioning
confidence: 99%
“…Folate has long been considered one such factor in number of observational studies. [2][3][4][5]7,8,15,31 Maternal folic acid supplementation in early pregnancy has been suggested to play a role in the prevention of nonsyndromic orofacial cleft, i.e. cleft lip with or without cleft palate (CL/P).…”
Section: Discussionmentioning
confidence: 99%
“…MTHFR gene A1298C locus was analyzed and shown positive and negative association with the cleft lip and palate [15,[69][70][71]. Despite the association between MTHFR C677T polymorphism and CL/P, there still needs more studies to be performed to indicate if the MTHFR gene polymorphism is the independent marker for the CL/P [72][73][74].…”
Section: Cleft Palatementioning
confidence: 99%
“…Eleven articles were found to be eligible for the inclusion in the present meta-analysis Grunert et al, 2002;Shoteresuk et al, 2003;van Roij et al, 2003;Pezzetti et al, 2004;Mills et al, 2008;Ali et al, 2009;Sozen et al, 2009;Chorna et al, 2011;SemicJusufagic et al, 2012;Kumari et al, 2013). All these eleven studies were performed in different countries: Argentina , Germany (Grunert et al, 2002), India (Ali et al, 2009;Kumari et al, 2013), Ireland (Mills et al, 2008), Italy (Pezzetti et al, 2004), Netherlands (van Roij et al, 2003), Thailand (Shoteresuk et al, 2003), Ukraine (Chorna et al, 2011), and Venezuela (Sozen et al, 2009).…”
Section: Eligible Studiesmentioning
confidence: 99%
“…All these eleven studies were performed in different countries: Argentina , Germany (Grunert et al, 2002), India (Ali et al, 2009;Kumari et al, 2013), Ireland (Mills et al, 2008), Italy (Pezzetti et al, 2004), Netherlands (van Roij et al, 2003), Thailand (Shoteresuk et al, 2003), Ukraine (Chorna et al, 2011), and Venezuela (Sozen et al, 2009). In one study, Ali et al (2009) reported only allele numbers (Table 1).…”
Section: Eligible Studiesmentioning
confidence: 99%